Tripod-shaped molecules: Synthesis and immobilization on Au(111) substrates - Sánches Molina, María; Sauter, Eric; Zharnikov, Michael (Applied surface science, 2019)
We describe design and synthesis of novel tripod-shaped molecules that are potentially capable of monomolecular assembly on noble metal substrates, maintaining, due to their rigidity and specific geometry, the orientation of the functional arm in a perpendicular fashion with respect to the substrate. Using a combination of X-ray photoelectron spectroscopy, X-ray absorption spectroscopy and atomic force microscopy, the ability of these molecules to form well-defined and densely packed self-assembled monolayers (SAMs) on Au(111) was demonstrated, with the majority of the molecules adsorbed in the predefined tripodal geometry, relying on the thiolate-gold anchors. The functionality of the respective monomolecular templates was proved by click reaction between the terminal alkyne groups of the monolayers and complementary azide-substituted substituent (theophylline), which served potentially as specific protein receptor. The resulting theophylline-terminated films were successfully tested for specific protein adsorption, verifying the validity and reliability of the presented concept, in terms of the tripod design and its “activation” by the click reaction.
Available online 09 November 2018
Gesehen am 13.02.2019